A CD64/FcγRI-mediated mechanism hijacks PD-1 from PD-L1/2 interaction and enhances anti-PD-1 functional recovery of exhausted T cells - Joo, Victor; Petrovas, Constantinos; de Leval, Laurence; Noto, Alessandra; Obeid, Michel; Fenwick, Craig; Pantaleo, Giuseppe (Frontiers in Immunology, 2023)
Therapeutic monoclonal antibodies (mAb) targeting the immune checkpoint inhibitor programmed cell death protein 1 (PD-1) have achieved considerable clinical success in anti-cancer therapy through relieving T cell exhaustion. Blockade of PD-1 interaction with its ligands PD-L1 and PD-L2 is an important determinant in promoting the functional recovery of exhausted T cells. Here, we show that anti-PD-1 mAbs act through an alternative mechanism leading to the downregulation of PD-1 surface expression on memory CD4+ and CD8+ T cells. PD-1 receptor downregulation is a distinct process from receptor endocytosis and occurs in a CD14+ monocyte dependent manner with the CD64/ Fc receptor I acting as the primary factor for this T cell extrinsic process. Importantly, downregulation of surface PD-1 strongly enhances antigen-specific functional recovery of exhausted PD-1+CD8+ T cells. Our study demonstrates a novel mechanism for reducing cell surface levels of PD-1 and limiting the inhibitory targeting by PD-L1/2 and thereby enhancing the efficacy of anti-PD-1 Ab in restoring T cell functionality.